Evaluating the Effects of Temporal Distance on Tourists’ Decision-Making Processes - Belinda, Ashioya; Beatrice, Imbaya; Sulo, Timothy (Journal of Tourism Management Research, 2021)
Kenya’s tourism continues to rely heavily on wildlife. Of the approximately 922,000 annual international arrivals during the peak season between June and October, nearly 738,000 head for the Maasai Mara National Game Reserve to witness the seventh wonder of the world, the annual wildebeest migration. Several studies have been conducted based on construal level theory to establish the effect of temporal distance using various factors that determine travel decisions. However, to date, no study has been carried out to establish the effect of temporal distance on destination choice decision-making. As tourism consumption involves making a purchase decision now for a future point in time, this study evaluated the effects of temporal distance on the destination choice decision-making based on the construal level theory framework. The study adopted the survey approach based on a confirmatory research design. Using a sample of 144 drawn from a population of 230 tourists, data was collected and analyzed using correlation, ANOVA, and regression methods. The findings revealed that temporal distance has a positive and significant effect on decision-making regarding destination choice based on levels of construal measured through R=0.324; R2=0.105; β = 0.295; t= 3.024 > +2; F=9.145; and p=0.003<0.05. The study revealed that temporal distance has a significant effect on the decision process of choosing a destination. In conclusion, therefore, marketing communications targeted at tourists should be intensified well in advance of the season envisioned for traveling to increase the desirability of the destination and thus, influence more tourists to choose the destination. The study also contributes valuably to the literature on tourists’ destination choosing decisions based on temporal distance in the construal level theory framework.